Design and implementation of low power consumption wireless sensor node - Djadour Imededdin; Aidel Salih; Hicham Medkour (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This work proposes an implementation of wireless sensor node characterized by its very low power consumption. The node comprises three main components: Xbee module, low power PIC microcontroller and digital sensor. The node can be set to sense then transmit data via one of two transmission methods: periodic and by interruptions. To evaluate the power consumption; currents in the node is measured during the different transmission stages for both methods. As a result, a significant reduction in the power consumption is shown particularly in sleep mode compared to conventional transmission methods. The characteristic of low power consumption makes the proposed node practically ecologic. It can also be fed with the extrem low power supplied by an energy harvesting system.